HB E / Thalassemia Beta - Saputra, Hendra; Saptino Miro (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Thalassemia is a blood disorder which characterized with decreased or absence of globin chain in red blood cell thus disrupted hemoglobin synthesis. Hb E/ β-Thalassemia is a thalassemia syndrome of intermedia severity with a very heterogeneous clinical spectrum. The most presented sign and symptoms in Hb E/ β-Thalassemia are pallor and abdominal mass enlargement. One of the most accurate and fast methods to diagnose thalassemia is High Performance Liquid Chromatography. Hb E/ β-Thalassemia based on clinical severity, can start with blood transfusions, and when serum ferritin level increased, it can also begin with iron chelation therapy to prevent complication from iron overload in the body. We have reported a case of a 28-year-old patient diagnosed with Hb E/ β-Thalassemia, with hemoglobin level is 5,1 g/dL and serum ferritin 1029 ng/mL, started to treat with blood transfusions and iron chelation therapy. Early detection on Hb E/ β-Thalassemia patient will give better outcome to prevent complications caused by the disease it self or treatment given.